Elevated Homocysteine Level and Brain Atrophy Changes as Markers to Screen the Alzheimer Disease: Case Series - Ram Prakash Sah; C. S. Vidya; Pratibha Pereira; Shubha Jayaram; Anshu Kumar Yadav; P. Sujatha (Annals of Geriatric Medicine and Research, 2024)
Alzheimer disease (AD) is the most common cause of dementia worldwide. Its clinical manifestations include a progressive loss of memory and other cognitive domains, as well as brain atrophy. An elevated homocysteine level (>15 µmol/L), known as hyperhomocysteinemia, is also an attributing risk factor for AD, vascular pathologies, and brain atrophy. Neuroimaging studies including T2-weighted magnetic resonance imaging scans revealed white matter hyperintensities in the periventricular and deep white matter, enlarged ventricles, widened sulci, and decreased white matter mass, which are features of aging, as well as cerebrovascular changes. This case series investigated changes in biochemical marker levels including serum homocysteine, folate, and vitamin B12, and the degree of atrophic variations in cortical-subcortical white matter in AD. The present study hypothesized that serum homocysteine levels might be used as a surrogate marker to screen for AD at an earlier stage.